Hypermethylation of Hif3a and Ifltd1 is associated with atrial remodeling in pressure-overload murine model - Keiko Abe; Tetsuo Sasano; Yurie Soejima; Haruhisa Fukayama; Shigeru Maeda; Tetsushi Furukawa (Scientific Reports)
Abstract Atrial remodeling is a major pathophysiological mechanism of atrial fibrillation (AF). Atrial remodeling progresses with aging and background diseases, including hypertension, heart failure, and AF itself. However, its mechanism of action and reversibility have not been completely elucidated. In this study, we investigated the involvement of DNA methylation in atrial remodeling. Mice underwent transverse aortic constriction (TAC) to generate a pressure overload model. After 14 days, the TAC-operated mice showed a significant increase in the atrium/body weight ratio and deposition of collagen fibers in the atria. A comprehensive analysis using RNA-sequencing (RNA-Seq) and methyl-CpG-binding domain sequencing (MBD-Seq) in the left atrial tissue identified Hif3a and Ifltd1 as showing increased DNA methylation in their promoter regions and decreased RNA expression. In addition, we created a transient pressure overload model by removing the aortic constriction 3 or 7 days after the initial TAC procedure (R3 or R7 groups). A reduction in RNA expression was achieved at R3 for Hif3a and at R7 for Ifltd1. Heterozygous Dnmt1 gene-targeting mice (Dnmt1 mut ) showed disappearance of the reduction in RNA expression and an increase in the atrium/body weight ratio. Altogether, DNA methylation contributed to at least part of atrial remodeling in the pressure overload mouse model.